2020
DOI: 10.1186/s13075-020-02168-1
|View full text |Cite
|
Sign up to set email alerts
|

Disease features associated with a low disease impact in patients with psoriatic arthritis: results of a cross-sectional multicenter study

Abstract: on behalf of the MAAPS study groupAbstract Background: Patient-reported outcomes measures, such as those provided by the Psoriatic Arthritis Impact of Disease (PsAID) questionnaire, have been found to be a reliable indicator of change during treatment, predictive of long-term outcomes, and the impact of psoriatic arthritis (PsA) on patients' lives. The objective of the study was to describe the demographic and clinical characteristics of PsA patients with a low disease impact and to analyze predictive factors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…This previously unreported nding has clear practical implications, in that not all currently available treatments for PsA address this domain with the same e cacy [22]. Nevertheless, the nding is in clear agreement with the results of another Spanish multicenter study, in which patients with distal interphalangeal joint involvement (most with associated nail disease) had signi cantly fewer possibilities of reaching a PsAID score indicating low impact of disease [23]. In a multicenter Turkish study, nail disease with involvement of the distal interphalangeal joint was identi ed as one of the main barriers for achieving minimal disease activity [24].…”
Section: Discussionsupporting
confidence: 81%
“…This previously unreported nding has clear practical implications, in that not all currently available treatments for PsA address this domain with the same e cacy [22]. Nevertheless, the nding is in clear agreement with the results of another Spanish multicenter study, in which patients with distal interphalangeal joint involvement (most with associated nail disease) had signi cantly fewer possibilities of reaching a PsAID score indicating low impact of disease [23]. In a multicenter Turkish study, nail disease with involvement of the distal interphalangeal joint was identi ed as one of the main barriers for achieving minimal disease activity [24].…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the PSAID questionnaire surely captures many patients’ perceptions that are not necessarily related to disease activity. For truly holistic care, there should be two treat-to-target goals, one based on an inflammation-derived measure and one on a patient-reported outcome [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter study found that patients with distal interphalangeal joint involvement, a family history of PsA, or high levels of Creactive protein (CRP) were less likely to achieve low disease impact according to PsAID [6]. In another multicenter study, a PsAID score indicating high disease impact (≥4) was associated with female sex, tender joints, enthesitis, and comorbid conditions [7].…”
Section: Introductionmentioning
confidence: 99%